DILEMATIKA KEBIJAKAN UPAH MINIMUM DALAM PENGUPAHAN DI INDONESIA - Wiryawan, I Wayan Gde (Jurnal Advokasi, 2016)
The existence of Pancasila Industrial Relations in Indonesia, which consists of three parties namely, employees, businessman and the government to put the governments role as a representative of the state in its strategic position as a regulator in an effort to provide protection to workers rights in the area of wages in order to enhance the dignity of workers. The minimum wage policy as a wage policy that is built sporadically result in not achieving the minimum wage essence of which is to protect workers wages from being hit in the low wage has caused dilematika in Industrial Relations in Indonesia. The controversy in the process of establishing, implementing and enforcing minimum wages will always happen when the construction of the minimum wage policy developed in the absence of wage system in the Pancasila Industrial Relations.